2001
DOI: 10.1002/hyp.235
|View full text |Cite
|
Sign up to set email alerts
|

Hillslope and wetland hydrodynamics in a tussock grassland, South Island, New Zealand

Abstract: Abstract:Previous research on two experimental catchments at the Glendhu Forest (Otago) showed that runoff dynamics from this landscape differ substantially from other areas in New Zealand. In particular, the recession curves from these catchments have two distinct phases: a rapid decline for a period of several hours, followed by a slow decline that may last many days to weeks. In the current study, soil water matric potential measurements indicated that perched saturated zones develop very rapidly in the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 8 publications
1
19
0
2
Order By: Relevance
“…Using various tracers, the end-member mixing analysis has been used to elucidate flow paths and hydrological processes in several catchments (e.g., Hooper et al, 1990;Elsenbeer et al, 1995;Katsuyama et al, 2001). Numerous conceptual models have adopted the flow path dynamics proposed by Anderson et al (1997), i.e., both pre-event soil water and bedrock groundwater contribute to the formation of a saturated zone in the area adjacent to the stream (e.g., McGlynn et al, 1999;Bowden et al, 2001;Uchida et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Using various tracers, the end-member mixing analysis has been used to elucidate flow paths and hydrological processes in several catchments (e.g., Hooper et al, 1990;Elsenbeer et al, 1995;Katsuyama et al, 2001). Numerous conceptual models have adopted the flow path dynamics proposed by Anderson et al (1997), i.e., both pre-event soil water and bedrock groundwater contribute to the formation of a saturated zone in the area adjacent to the stream (e.g., McGlynn et al, 1999;Bowden et al, 2001;Uchida et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of interflow in producing stormflow has been demonstrated by earlier workers (Miller, 1994;Bowden et al, 2001). Bowden et al (2001) showed that lateral flow in the thin Organic and A Horizon layers was substantial and probably often emerged as flow over the wetland surface in high quickflow events, contributing to the new water inputs to the streams. They identified slow drainage from deep loess horizons (layers B and C) as the source of the extended baseflow in the catchments.…”
Section: Source Of Old Componentmentioning
confidence: 83%
“…Samples were collected from two tubes permanently inserted in the central wetland of GH5 (Fahey et al, 1998;Bowden et al, 2001). One was a piezometer tube drawing from 1 m depth near the mid-bog piezometer nest, the other from an aluminium tube drawing from 1.2 m depth near the lower piezometer nest.…”
Section: Tritium and Other Patternsmentioning
confidence: 99%
See 2 more Smart Citations